2019
DOI: 10.1101/572941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytokinin functions as an asymmetric and anti-gravitropic signal in lateral roots

Abstract: 31Directional organ growth allows the plant root system to strategically cover its 32 surroundings. Intercellular auxin transport is aligned with the gravity vector in 33 the primary root tips, facilitating downward organ bending at the lower root 34 flank. Here we show that cytokinin signaling functions as a lateral root specific 35 anti-gravitropic component, promoting the radial distribution of the root system. 36 We performed a genome-wide association study and revealed that signal peptide 37 processing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Binenbaum et al (2018). observed that there are other hormones such as cytokinins and gibberellic acid, which affect the root shape by increasing its length and development while reducing ethylene levels (Waidmann et al 2019) Additionally, Plazas et al (2019) found that the combination of PGPRs and BR s can improve soil hydration rate by playing a crucial signal between ecological conditions and roots as it has been presented in (Mustafa et al 2023). Hence, when Brassinosteroid is used in conjunction with rhizobacterial strains, plants absorb nutrients and more water from the soil; greatly increasing root absorption area without negative behavior (Mustafa et al 2022).…”
Section: Discussionmentioning
confidence: 88%
“…Binenbaum et al (2018). observed that there are other hormones such as cytokinins and gibberellic acid, which affect the root shape by increasing its length and development while reducing ethylene levels (Waidmann et al 2019) Additionally, Plazas et al (2019) found that the combination of PGPRs and BR s can improve soil hydration rate by playing a crucial signal between ecological conditions and roots as it has been presented in (Mustafa et al 2023). Hence, when Brassinosteroid is used in conjunction with rhizobacterial strains, plants absorb nutrients and more water from the soil; greatly increasing root absorption area without negative behavior (Mustafa et al 2022).…”
Section: Discussionmentioning
confidence: 88%
“…Cytokinin-activating enzymes are in charge of cytokinin activation (Kurakawa et al, 2007), and the repressed expression of these genes in roots may contribute to establishing connections to their host through a developed lateral root system in parasitic plants as a decrease in cytokinin levels in roots can enhance lateral root growth (Waidmann et al, 2019). Notably, this is not conserved among parasitic plants because the LTR-associated cytokinin-activating enzyme genes were not present in S. asiatica (Table S21).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 6 and 1 cytokinin-activating-enzyme-related genes with barely detectable expression were separately found in superset-type and overlap-type genes (Table S10). Cytokinin activating enzyme in rice has been reported to work in the final step of bioactive cytokinin synthesis (Kurakawa et al, 2007), and cytokinin in roots could inhibit root initiation though directly acting on lateral root founder cells (Waidmann et al, 2019). The repressed expression of these genes in the roots of P. kansuensis may enhance lateral root growth and contribute to the establishment of parasitic associations for improving the survival fitness of parasites.…”
Section: Phylogenetic Analysis Based On Ltr-rts Reverse Transcriptase...mentioning
confidence: 99%
“…Mechanism III suggests that root exploration of the soil by LRs depends on CK concentration (Figure 1D). Waidmann et al, (2019) showed that CK signalling affects root gravitropic growth. In particular, asymmetric CK signalling reduces growth at the upper side of recently emerged LRs, but not in PRs.…”
Section: Rsa Determinantsmentioning
confidence: 99%
“…CKX enzymes are responsible for the irreversible degradation of CK via the oxidative cleavage of their side chain, thus blocking CK accumulation. The inactive CKX2 variant shared by specific Arabidopsis accessions, besides allowing better acclimation to extreme winters (Xiao and Zhang, 2020), promotes a shallower RSA and seems to be a promising trait to cope with hypoxic stress (Waidmann et al, 2019). Indeed, CK signalling plays an important role in adaptation to hypoxia.…”
Section: Rsa Determinantsmentioning
confidence: 99%